2019
DOI: 10.1177/0046958019842001
|View full text |Cite
|
Sign up to set email alerts
|

Sleep—an Essential Component of Obesity Screening and Counseling: A Policy Analysis of the Affordable Care Act

Abstract: The Patient Protection and Affordable Care Act (PPACA) has provided access to health care for millions of people in the United States. One of the most beneficial aspects of the PPACA is the obesity screening and counseling provision. Currently, it is estimated that over 39% of US adults are obese. Research has linked sleep disturbances to obesity and obesity-related behaviors. The purpose of this article is to advocate for evidence-based care through the inclusion of sleep disturbance screening and management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Some researchers have suggested that sleep health should be considered an essential component of screening and counseling for weight management for several reasons [ 5 ]. First, sleep health characteristics including sleep duration, sleep timing, sleepiness and sleep regularity, are associated with weight gain and obesity independent of physical activity and diet [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have suggested that sleep health should be considered an essential component of screening and counseling for weight management for several reasons [ 5 ]. First, sleep health characteristics including sleep duration, sleep timing, sleepiness and sleep regularity, are associated with weight gain and obesity independent of physical activity and diet [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%